Proteção constitucional/internacional do direito à razoável duração do processo - Abdala, Kaliny Belchior (2008)
This work about an analysis of the movement for the protection of human rights in the Brazilian legal system after the Constitutional Amendment n. 45/2004, which raised the procedural right to speed the constitutional precept, broadening the understanding to the international order. The study begins with the history of the process of internationalization of these rights, through the global system and regional systems. It examines, in particular, the Inter-American System of protection of human rights, currently represented by the OAS - Organization of American States, to which the Brazilian state is bound. Moth a sketch about the constitutionality of the treaties that Brazil is a part, as is done to intervene in member states, as well as the effectiveness and implementation of the decisions of the Inter Court in the Brazilian state. Finally, analyzes the profile of domestic jurisdiction and the mechanisms used for a more rapid access to justice, avoiding the extinction of rights